The book of George : a novel - Greathead, Kate (Henry Holt and Company, 2024)
"From the author of the critically acclaimed Laura & Emma comes a The Love Affairs of Nathaniel P. for our times: Kate Greathead's razor-sharp but big-hearted excavation of millennial masculinity, The Book of George. If you haven't had the misfortune of dating a George, you know someone who has. He's a young man brimming with potential but incapable of following through; noncommittal to his long-suffering girlfriend, Jenny; distant from but still reliant on his mother; funny one minute, sullenly brooding the next. Here, Kate Greathead paints one particular, unforgettable George in a series of droll and surprisingly poignant snapshots of his life over two decades. And yet, it's hard not to root for George at least a little. Beneath his cynicism is a reservoir of fondness for Jenny's valiant willingness to put up with him. Each demonstration of his flaws is paired with a self-eviscerating comment. No one is more disappointed in him than himself (except maybe Jenny and his mother). As hilarious as it is astute and singular as it is universal, The Book of George is a deft, unexpectedly moving portrait of millennial masculinity"--